The Moderating Role of Sustainability Disclosure in the Association between Tax Avoidance and Cost of Debt - Amrie Firmansyah; Irfan Fauzi; Muchamad Rizal Pua Geno; Dani Kharismawan Prakosa; Adhitya Jati Purwaka (WIM Solusi Prima, 2023)
Company funding can derive from debt and shares. Managers' funding decisions have an impact on the costs that the company must bear. Even though it has high risks and many requirements, managers use much debt in company funding. The company must bear the debt costs associated with this funding. This research examines the effect of tax avoidance on the cost of debt. This research also uses sustainability disclosure as a moderating variable. This research uses manufacturing company financial report data from www.idnfinancials.com from 2016 to 2020. Based on purposive sampling, the total number of observations can be used in this research is 276. Hypothesis testing was carried out using multiple linear regression analysis for cross-section data. This research concludes that tax avoidance positively affects the cost of debt. This research also finds that sustainability disclosure strengthens the positive influence of tax avoidance on the cost of debt. This research contributes to providing literature on the role of sustainability implemented in companies in one of the developing countries. This implementation can be associated with managerial decisions that may not always align with the interests of company owners.